Role of public relations practices in content management: the mediating role of new media platforms - Al Hadeed, Ali Yahya; Maysari, Ihsan; Aldroubi, Mohammad Mahmoud; Attar, Razaz Waheeb; Al Olaimat, Farhan; Habes, Mohammed (Frontiers in Sociology, 2024)
Public relations practices are widely accompanied by communication and persuasion. Especially today, when new media platforms provide direct accessibility, communication through PR has become more improved. This research focused on media organizations in the UAE, with a special consideration given to their audience content management. The researchers applied the case study method and selected a sample of n = 280 individuals from n = 12 media houses currently working in the UAE. The results obtained by structural equation modeling (SEM) revealed that media organizations in the UAE pay significant consideration to public relations practices (p > 0.000) and new media adoption (p > 0.000). Moreover, both these public relations practices (p > 0.000) and new media adoption were also found to significantly focus on two-way communication. Consequently, this two-way communication is significantly affecting content management among these organizations (p > 0.000), leading to the design, evaluation, and alteration of content that is acceptable and liked by their audiences. Thus, it has been concluded that media content and its management is not a simple task. Audience and communication are two basic factors that play an important role in this regard. Furthermore, the role of public relations practices also enhances communication and content management practices, leading to even more constructive outcomes.